2017
DOI: 10.1007/978-3-319-66299-2_7
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Use of Mutation Analysis for Automated Program Repair

Abstract: Abstract. Research in Search-Based Automated Program Repair has demonstrated promising results, but has nevertheless been largely confined to small, single-edit patches using a limited set of mutation operators. Tackling a broader spectrum of bugs will require multiple edits and a larger set of operators, leading to a combinatorial explosion of the search space. This motivates the need for more efficient search techniques. We propose to use the test case results of candidate patches to localise suitable fix lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Further improvements in G&V repair hinge on the capability of improving the precision of fault localization. A promising option is using mutation-based fault localization, which was recently investigated [44] on data from the BugZoo 3 repair benchmarks. [44] found no significant improvement on the overall repair performance-supposedly because the single-edit mutations used in the study may be too simple to reveal substantial differences between programs variants.…”
Section: B Automated Program Repairmentioning
confidence: 99%
“…Further improvements in G&V repair hinge on the capability of improving the precision of fault localization. A promising option is using mutation-based fault localization, which was recently investigated [44] on data from the BugZoo 3 repair benchmarks. [44] found no significant improvement on the overall repair performance-supposedly because the single-edit mutations used in the study may be too simple to reveal substantial differences between programs variants.…”
Section: B Automated Program Repairmentioning
confidence: 99%
“…Ways to seed faults include mutating the programs using techniques common in mutation testing or seeding a known error into the code. One way to seed a realistic error is to use the edit history of a program's source code to find a change that repaired a bug, then re-introduce the corresponding 'buggy' code into the SUT [33]. Note that obtaining faulty executions by seeding faults does not limit LLANALYZER to only programs for which source code exists because faults can be seeded at any level, including in machine code.…”
Section: Corpus Generationmentioning
confidence: 99%
“…The intuition behind these techniques is that when mutants are generated at the faulty location, the test suite should exhibit different behavior than when mutants are generated in non-faulty locations. Further studies [163,198] have suggested that MBFL techniques do not significantly distinguish between faulty and non-faulty locations. Smith et al [187] compare the performance of single patches to N-version patches, where the behavior of the N-version patches is described by a voting system.…”
Section: Software Diversitymentioning
confidence: 99%